α7 Nicotinic Receptor Promotes the Neuroprotective Functions of Astrocytes against Oxaliplatin Neurotoxicity - Lorenzo Di Cesare Mannelli; Barbara Tenci; Matteo Zanardelli; Paola Failli; Carla Ghelardini (Neural Plasticity)
Neuropathies are characterized by a complex response of the central nervous system to injuries. Glial cells are recruited to maintain neuronal homeostasis but dysregulated activation leads to pain signaling amplification and reduces the glial neuroprotective power. Recently, we highlighted the property of α7 nicotinic-acetylcholine-receptor (nAChR) agonists to relieve pain and induce neuroprotection simultaneously with a strong increase in astrocyte density. Aimed to study the role of α7 nAChR in the neuron-glia cross-talk, we treated primary rat neurons and astrocytes with the neurotoxic anticancer drug oxaliplatin evaluating the effect of the α7 nAChR agonist PNU-282987 (PNU). Oxaliplatin (1 μM, 48 h) reduced cell viability and increased caspase-3 activity of neuron monocultures without damaging astrocytes. In cocultures, astrocytes were not able to protect neurons by oxaliplatin even if glial cell metabolism was stimulated (pyruvate increase). On the contrary, the coculture incubation with 10 μM PNU improved neuron viability and inhibited apoptosis. In the absence of astrocytes, the protection disappeared. Furthermore, PNU promoted the release of the anti-inflammatory cytokine TGF-β1 and the expression of the glutamate-detoxifying enzyme glutamine synthetase. The α7 nAChR stimulation protects neurons from oxaliplatin toxicity through an astrocyte-mediated mechanism. α7 nAChR is suggested for recovering the homeostatic role of astrocytes.